Ferromagnetism in metal oxide systems: interfaces, dopants, and defects - Thakare, Vishal P.; Game, Onkar S.; Ogale, Satishchandra B. (Journal of Materials Chemistry C, 2013)
Ferromagnetism in metal oxide systems has always attracted scientific attention in view of the intriguing and interesting interplay of spin, charge, orbital and lattice degrees of freedom that such systems display. This trend appears to be continuing with enhanced focus on interface systems, multiferroics, diluted magnetic semiconducting oxides (DMSOs) and nanomaterial magnetism. Newer techniques are being applied to bring out materials issues that are critical to the precise understanding of the origin of magnetism in certain cases. Interest is also beginning to grow in exploring application potential of some such systems. In this article we review the developments in this field by late 2011 and 2012.